PCB/IC fault analysis with FRA techniques - Win Niang. (2008)
A new novel technique is developed and verified to identify the manufacturing faults in PCB and ICs. The technique is known as frequency response analysis by which the impedance responses of tracks are measured up to a frequency limit of 13 MHz. The response function is analyzed using Matlab frequency response zero and pole fitting.